Insights into neoadjuvant chemotherapy efficacy for stage 1B3 locally advanced cervical cancer: case series - Gupta, Sumedha; Gupta, Ratika; Shamsunder, Saritha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cervical cancer remains a leading cause of mortality among women worldwide, particularly in developing nations. While radical surgery is the established standard of care for early-stage disease, pelvic relapse post-surgery remains a concern. Neoadjuvant chemotherapy (NACT) preceding radical surgery has emerged as a promising approach, aiming to reduce tumor burden and improve surgical outcomes. We present three cases of stage 1B3 cervical cancer treated with three cycles of NACT repeated three weekly followed by radical hysterectomy. Post-operatively two patients received radiotherapy (External beam radiotherapy and brachytherapy) and one patient got lost to follow-up for 6 months and did not receive post-operative radiotherapy now under observation and regular follow-up. All the patients exhibited significant tumor reduction following chemotherapy, enabling successful surgical intervention. All patients remained in remission post-treatment. NACT showed effectiveness in reducing tumor size and facilitating successful radical surgery in patients with stage 1B3 cervical cancer. Our case series highlights the potential of NACT followed by radical surgery as a promising therapeutic strategy for stage 1B3 cervical cancer. NACT facilitated successful surgical intervention with favourable outcomes. Further research is warranted to elucidate the optimal patient selection criteria and the long-term benefits of this approach in improving survival rates and quality of life for cervical cancer patients.